A preliminary Study on Anticancer and Antimicrobial Potential of Methanolic Extracts of Verbascum napifolium - TAŞKAYA, Aylin; ŞAHİN, Burcu and CEYHAN GÜVENSEN, Nur and MAMMADOV, Ramazan (ISPEC Journal of Agricultural Sciences, 2023)
Plants are widely used in the treatment of many diseases. This study evaluates for the first time the potential anticancer and antimicrobial activities of methanol extracts of leaves and flower parts of Verbascum napifolium, an endemic species distributed in the flora of Turkey. The antimicrobial activities were evaluated by the disc diffusion method and by determining the minimal inhibitory concentration (MIC). In all bacteria, flower methanol extract was found to be more sensitive. Escherichia coli was determined to be more sensitive to both extracts compared to all tested bacteria. These results suggest that V napifolium possess potential important anticancer and antimicrobial activities. The anticancer activities the effect of Verbascum napifolium flower and leaf methanol extracts on cell viability in CaCo-2 and L929 cell lines were determined by MTT assay. Flower methanol extract of Verbascum napifolium showed a better anticancer potential than the leaf methanol extract.